Large deviations and metastability - Olivieri, Enzo, 1945-; Vares, Maria Eulália. (Cambridge, UK ; New York : Cambridge University Press, 2005)
The book provides a general introduction to the theory of large deviations and a wide overview of the metastable behaviour of stochastic dynamics. Written to be accessible to graduate students, this book provides an excellent route into contemporary research.
Cover; Half-title; Series-title; Title; Copyright; Dedication; CONTENTS; PREFACE; 1 Large deviations: basic results; 2 Small random perturbations of dynamical systems. Basic estimates of Freidlin and Wentzell; 3 Large deviations and statistical mechanics; 4 Metastability. General description. Curie-Weiss model. Contact process; 5 Metastability. Models of Freidlin and Wentzell; 6 Reversible Markov chains in the Freidlin-Wentzell regime; 7 Metastable behaviour for lattice spin models at low temperature; REFERENCES; Index.
Includes bibliographical references (pages 493-506) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Large deviations; Stability; Grandes déviations.; Stabilité.; stability; MATHEMATICS -- Probability & Statistics -- General; Large deviations; Stability